Análisis de la evolución de la fibra de alpaca peruana del 2010 al 2019 - Azabache Alvarado, Diego Alonso (2021)
This research explores the Peruvian alpaca industry in the period between 2010 and 2019. The alpaca industry has seen growth in recent years, not only in terms of consumption but also in terms of exports, presenting new challenges and opportunities for the industry and stakeholders. The research details the levels presented by alpaca fiber in terms of production and exports, as well as some of the conflicts present in the industry in the recent years. For the analysis, quantitative information regarding alpaca industry was extracted as well as the collection of qualitative information about the production process or the conflict present in the industry for its development. Although the research allows to conclude that the alpaca industry presents a positive trend, it is important to note that competition from other countries, as well as conflicts inherent to the industry and the country, can lead to a reduction in the value of the fiber in the market international.